A new species of Aplectana (Nematoda: Cosmocercidae) in the Marsupial frog Gastrotheca microdiscus (Amphibia: Hemiphractidae) from Brazil - Alcantara, Edna P. [UNESP]; Ferreira-Silva, Cristiana [UNESP]; Forti, Lucas R.; Morais, Drausio H.; Silva, Reinaldo J. [UNESP] (Magnolia Press, 2021)
Aplectana longa n. sp. (Ascaridida: Cosmocercidae) from the small intestine of Gastrotheca microdiscus (Amphibia: Hemiphractidae) is described and illustrated. The new species is characterized by the combination of a unique set of morphological characters: 1) Large body size in both sexes; 2) Lateral alae absent; 3) Gubernaculum present, small, thin, weakly sclerotized, pointed at the distal end and curved proximally at the end, with a small and punctiform papilla-like dilation, and 4) Caudal papillae arrangement (9+1:0:6). The distribution pattern of caudal papillae is similar only to Aplectana chamaeleonsis. Nevertheless, Aplectana longa n. sp. is easily differentiated from this species by the arrangement of precloacal papillae. This is the 57th species of the Aplectana and the 16th species reported from Brazil.
Keywords: Anura; Nematoda; Neotropical region; Parasite; South America